2022
DOI: 10.1017/s0033291721005195
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors that distinguish between men and women who have suicidal thoughts and attempt suicide: findings from a national probability sample of adults

Abstract: Background Previous research has highlighted the importance of understanding which psychosocial factors distinguish between those with suicide thoughts compared to those who attempt suicide. This study aims to investigate these distinguishing factors further within an ideation-to-action framework and to explore sex differences in suicide risk. Methods Participants (n = 7546, aged 16+) were from the cross-sectional Adult Psychiatric Morbidity Survey (APMS; 2014) of England. Face-to-face a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 42 publications
1
13
2
Order By: Relevance
“…We did descriptive analyses on the whole sample as well as gender-stratified (given the epidemiology of suicidality 19 and IPV differs between men and women 20 ). We examined the extent to which associations between each IPV indicator and past-year self-harm and suicidality could be explained by other factors.…”
Section: Methodsmentioning
confidence: 99%
“…We did descriptive analyses on the whole sample as well as gender-stratified (given the epidemiology of suicidality 19 and IPV differs between men and women 20 ). We examined the extent to which associations between each IPV indicator and past-year self-harm and suicidality could be explained by other factors.…”
Section: Methodsmentioning
confidence: 99%
“…Across the breadth of self-initiated coping strategies surveyed, those most often mentioned were efforts to adapt socially through transitioning to digital communication, alongside staying occupied with or without screens, exercising, and connecting with nature or otherwise leaving the house. Noteworthy mental health stressors and coping findings are contextualized in line with existing understanding around masculinity (Seidler et al, 2016), mental health (Richardson et al, 2022) and the burgeoning COVID-19 literature (Greenglass et al, 2021;Livingston et al, 2021;Ogrodniczuk et al, 2021) below.…”
Section: Discussionmentioning
confidence: 90%
“…While we cannot unequivocally infer the extent to which social isolation occurred alongside job loss, for example, alleviating feelings of isolation is nevertheless crucial in protecting men’s mental health. Evidence from recent survey research suggests that only social support was protective against the transition from suicidal thoughts to suicide attempts in men ( Richardson et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Wan et al illustrated non-suicidal self-injury, suicidal ideation and suicide attemptwere significantly associated with increased ACEs in community adolescent populations ( 16 ). Emerging research also demonstrates ACEs during childhood contributes to health consequences in later adulthood ( 18 20 ). Among college students, studies have demonstrated that ACEs is associated with risk behaviors, and mental health ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%